2022
DOI: 10.1039/d2fo02102a
|View full text |Cite
|
Sign up to set email alerts
|

Dietary astaxanthin-rich extract ameliorates atherosclerosis/retinopathy and restructures gut microbiome in apolipoprotein E-deficient mice fed on a high-fat diet

Abstract: Scope: Atherosclerosis (AS) is the leading cause of ischemic disease. However, the anti-AS effects of astaxanthin and its potential mechanisms remain unclear. This study aimed to investigate the function of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…LefSE analysis identified that Akkermansia was the only bacteria with a relative abundance change exceeding 1% in the AX group compared to the HFD group. Numerous studies had reported a growth of Akkermansia following AX supplementation [ 37 , 38 , 62 ]. A decreased abundance of Akkermansia was associated with various diseases such as obesity, diabetes and liver steatosis, while Akkermansia supplementation exhibited anti-obesity effects and improve metabolic disorders induced by HFD [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LefSE analysis identified that Akkermansia was the only bacteria with a relative abundance change exceeding 1% in the AX group compared to the HFD group. Numerous studies had reported a growth of Akkermansia following AX supplementation [ 37 , 38 , 62 ]. A decreased abundance of Akkermansia was associated with various diseases such as obesity, diabetes and liver steatosis, while Akkermansia supplementation exhibited anti-obesity effects and improve metabolic disorders induced by HFD [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…An improved strategy targeting gut dysbiosis could help reduce inflammation and rescue muscle strength [36]. Studies have confirmed the probiotic and anti-gut inflammatory properties of AX in mice fed HFD [37][38][39]. Gut microbiota plays a crucial role in connecting food intervention with disease improvement, as it can be directly influenced by diet.…”
Section: Introductionmentioning
confidence: 99%